Contextualization and Context Effects: An Integrative Review of Studies on the Outcomes of Diversity Management Practices - Anna Schlueter; Stefan Gold (Corporate Social Responsibility and Environmental Management, 2025)
Research on the outcomes of diversity management practices has produced inconsistent and even contradictory results. It has been argued that these discrepancies are due to contextual differences between studies. Building on this argument, this integrative review provides an in-depth analysis of context, aiming to gain a deeper understanding of the outcomes of diversity management practices. We used Johns' categorical framework to synthesize the literature and systematically review contextualization and context effects in empirical studies. We offer suggestions for future contextualization, point to under- and unexplored contextual factors, outline ways to advance theorizing, and argue for more complex conceptualizations of contextual factors.
Keywords: 650; context effects; contextualization; diversity management practices; integrative review